A Combined Thermodynamics & Computational Method to Assess Lithium Composition in Anode and Cathode of Lithium Ion Batteries. (1st October 2016) - Zhang, Wenyu; Jiang, Lianlian; Van Durmen, Pauline; Saadat, Somaye; Yazami, Rachid
Abstract: With aim to address the open question of accurate determination of lithium composition in anode and cathode at a defined state of charge (SOC) of lithium ion batteries (LIB), we developed a method combining electrochemical thermodynamic measurements (ETM) and computational data fitting protocol. It is a common knowledge that in a lithium ion battery the SOC of anode and cathode differ from the SOC of the full-cell. Differences are in large part due to irreversible lithium losses within cell and to electrode mass unbalance. This implies that the lithium composition range in anode and in cathode during full charge and discharge cycle in full-cell is different from the composition range achieved in lithium half-cells of anode and cathode over their respective full SOC ranges. To the authors knowledge there is no unequivocal and practical method to determine the actual lithium composition of electrodes in a LIB, hence their SOC. Yet, accurate lithium composition assessment is fundamental not only for understanding the physics of electrodes but also for optimizing cell performances, particularly energy density and cycle life.